The 2nd International Electronic Conference on Foods—“Future Foods and Food Technologies for a Sustainable 2021
DOI: 10.3390/foods2021-10962
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulsed Electric Fields on the Recovery of Antioxidant Protein Extracts from Fish Side Streams

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Martí‐Quijal et al. (2023) used PEF to extract the active ingredients in the head, skin, viscera, and backbone of sea bass. It was found that PEF treatment could improve the extraction rate of protein and the recovery rate of basic minerals, reduce the residual of heavy metals, and enhance the antioxidant activity and the formation of bioactive peptides in the skin and head extracts.…”
Section: Application In Prefabricated Aquatic Foodsmentioning
confidence: 99%
“…Martí‐Quijal et al. (2023) used PEF to extract the active ingredients in the head, skin, viscera, and backbone of sea bass. It was found that PEF treatment could improve the extraction rate of protein and the recovery rate of basic minerals, reduce the residual of heavy metals, and enhance the antioxidant activity and the formation of bioactive peptides in the skin and head extracts.…”
Section: Application In Prefabricated Aquatic Foodsmentioning
confidence: 99%